Designing experiential educational tourism for youth environmental behavior change: A river cleanup management model - Eldo Delamontano; Cipta Endyana; Yunus Winoto; Evi Novianti (Sustinere: Journal of Environment and Sustainability, 2026)
This study develops and validates a strategic management model for experiential educational tourism aimed at fostering Pro-Environmental Behavior (PEB) among youth. Addressing a critical research gap, this research provides an empirically tested framework linking field-based interventions to measurable behavioral outcomes. Rooted in Kolb's Experiential Learning Theory (ELT), the quantitative study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) using data collection from 30 high school students (n = 30) participating in a River Cleanup program, an educational tourism activity integrating storytelling and environmental restoration work. Survey instruments assessed constructs including awareness, knowledge, motivation, participation, and behavior. The results confirmed the reliability of the proposed framework, explaining 69.5% of the PEB variance  (R2 = 0.695). Crucially, motivation to preserve nature (β = 0.471; p = 0.010) and environmental knowledge (β = 0.312; p=0.024) emerged as the strongest and most significant predictors. The large effect size of motivation (f2 = 0.308) underscores the importance of affective and normative components, aligning with Value-Belief-Norm (VBN) Theory, over mere physical participation. Although limited by the small sample size, this research demonstrates that strategically managed experiential intervention can significantly influence youth environmental behavior. This paper contributes to the literature by bridging tourism, environmental education, and management science, while offering a validated model for designing scalable sustainability programs.